Extending value stream mapping through waste definition beyond customer perspective. Issue 12 (28th March 2014) - Khurum, Mahvish; Petersen, Kai; Gorschek, Tony
ABSTRACT Value stream mapping (VSM) is one of the several Lean practices, which has recently attracted interest in the software engineering community. In other contexts (such as military, health and production), VSM has achieved considerable improvements in processes and products. The goal is to capitalize on these benefits in the software intensive product development context. The primary contribution is that we are extending the definition of waste to fit in the software intensive product development context. As traditionally in VSM everything that is not considered valuable is waste, we do this practically by looking at value beyond the customer perspective and using the software value map. An evaluation has been conducted through an industrial case study. First, the instantiation and motivations for selecting certain strategies have been provided. Second, the outcome of the VSM is described in detail. The instantiation of VSM via workshops was considered good as workshops allowed active interaction and discussion stakeholders' groups that are distant from each other in the regular work. With respect to waste and improvement identification, the participants were able to identify similar improvement suggestions. In a retrospective, the value stream approach was perceived positively by the practitioners with respect to process and outcome. Copyright © 2014 John Wiley & Sons, Ltd.